Dream West : politics and religion in cowboy movies - Brode, Douglas, 1943- (Jack and Doris Smothers series in Texas history, life, and culture, 2013)
"Overturns conventional thinking that the Western genre is essentially conservative. Instead, Brode demonstrates that Hollywood liberals used Westerns to espouse a progressive agenda on a range of issues, including gun control, environmental protection, respect for non-Christian belief systems, and community cohesion versus rugged individualism. Doug Brode takes a new look at dozens of Westerns, including Gunfight at the O.K. Corral, Red River, 3:10 to Yuma (old and new), The Wild Ones, High Noon, My Darling Clementine, The Alamo, and No Country for Old Men"--